Salvage esophagectomy under bilateral thoracotomy after definitive chemoradiotherapy for aorta T4 thoracic esophageal squamous cell carcinoma: Report of a case. (2015) - Nagaki, Yushi; Sato, Yusuke; Motoyama, Satoru; Yoshino, Kei; Sasaki, Tomohiko; Wakita, Akiyuki; Imai, Kazuhiro; Saito, Hajime; Minamiya, Yoshihiro
Highlights: The following case report describes the therapeutic course of a patient diagnosed with advanced thoracic esophageal squamous cell carcinoma invading the descending aorta. This is the first report of a salvage esophagectomy through a right thoracotomy followed by observation of the aortic invasion site through a left thoracotomy in a patient with T4b locally advanced esophageal squamous cell carcinoma. Abstract: Introduction: The surgical technique for esophagectomy to treat esophageal malignancies has been improved over the past several decades. Nevertheless, it remains extremely difficult to surgically treat patients with locally advanced T4b tumors invading the aorta or respiratory tract. Presentaion of case: A 37-year-old Japanese man was diagnosed with T4b (descending aorta) N2M0, Stage IIIC middle thoracic esophageal squamous cell carcinoma. He was initially treated with definitive CRT followed by 3 courses of DCF. After the DCF, CT showed that the main tumor had shrunk and appeared to have separated from the descending aorta. Therefore we decided to perform a salvage esophagectomy. Because we needed the ability to closely observe the site of invasion to determine whether aortic invasion was still present, half the esophageal resection was performed under right thoracotomy, but the final resection at the invasion site was performed under left thoracotomy. Consequently, the thoracic esophagus was safely removed and aortic replacement was avoided. The patient has now survived more than 30 months after the salvage esophagectomy with no additional treatment for esophageal cancer and no evidence of recurrent disease. Discussion: Because this and the previously reported procedures, each have particular advantages and disadvantages, one must contemplate and select an approach based on the situation for each individual patient. Conclusion: Salvage esophagectomy through a right thoracotomy followed by careful observation of the invasion site for possible aortic replacement through a left thoracotomy is an optional procedure for these patients.